Geotechnical condition of slopes at a proposed pipeline crossing, Great Bear River valley, Northwest Territories - Savigny, K. W.; Morgenstern, N. R. (Canadian Geotechnical Journal, 1986)
An in situ analysis of naturally occurring creep has been carried out in ice-rich permafrost soils underlying a slope at the proposed Canadian Arctic Gas pipeline crossing of Great Bear River in the Northwest Territories. This is the second of four papers that describe the study. Field investigation and instrument installation techniques are described and geological, geotechnical, and geothermal results are presented. The data presented here are intended to facilitate clear interpretation of deformation observations in the third paper. The data are representative of ice-rich glaciolacustrine clay deposits that are widespread in the mid-Mackenzie Valley area. Key words: Mackenzie Valley, pipelines, slopes, permafrost, soils, drilling, sampling, geotechnical, geothermal.